To design a network model of precedents, outcomes and mediators of teachers - Maryam Shamsifar; Hasanali Veiskarami; Masoud Sadeghi; Firoozeh Ghazanfari (Shahid Beheshti University of Medical Sciences, 2019)
Background:This study aimed at designing and testing a   model of precedents, outcomes and mediators of psychological empowerment in   teachers in Khoramabad. Method: The research is a correlation research via   structural equations modeling. Population of study is all high school   teachers in Khoramabad, 380 teachers were selected by multistage clustering   method as sample. Research tools were Misha-Spreitzer psychological   empowerment questionnaire, Kappa Aydin et al self-regulatory questionnaire,   Patterson job performance questionnaire, Blanchard-Hersey leadership styles   questionnaire, researcher made structural empowerment questionnaire and   Woolfok and Shanen-Moran self-efficacy questionnaire.  Results:Results showed that developed network fit   with data. Justifying and participatory leadership style and also structural   empowerment had causal and indirect effects on job performance with   psychological empowerment mediation. According to reported results,   psychological empowerment and self-regulatory mediate the relationship between   justifying style with job performance and structural empowerment with job   performance. Conclusion: According to the results of this study, the   education organization can plan to improve psychological empowerment ،self-regulation,self-efficacy of teachers and   change leadership styles and structural empowerment  for having teachers with good job   performance.